2022
DOI: 10.3390/antiox11122330
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Insight of Resveratrol Activated SIRT1 Interactome through Proximity Labeling Strategy

Abstract: SIRT1 functions by regulating the modification of proteins or interacting with other proteins to form complexes. It has been widely studied and found to play significant roles in various biological processes and diseases. However, systematic studies on activated-SIRT1 interactions remain limited. Here, we present a comprehensive SIRT1 interactome under resveratrol stimulation through proximity labeling methods. Our results demonstrated that RanGap1 interacted with SIRT1 in HEK 293T cells and MCF-7 cells. SIRT1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…Reduced expression of MQC genes could be also a consequence of downregulation of multiple signalling pathways and transcription factors. For example, SIRT1, which was downregulated in our study, can activate several transcription factors related to mitochondrial biogenesis and mitophagy 24 …”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Reduced expression of MQC genes could be also a consequence of downregulation of multiple signalling pathways and transcription factors. For example, SIRT1, which was downregulated in our study, can activate several transcription factors related to mitochondrial biogenesis and mitophagy 24 …”
Section: Discussionmentioning
confidence: 56%
“…Despite unaltered PARGC1 expression, we observed reduced expression of key transcription factors, NRF1 that regulates expression of nuclear DNA‐encoded mitochondrial genes and TFAM that reguates expression of mitochondrial DNA‐encoded mitochondrial genes. SIRT1 and mTOR have ability to activate PGC‐1α, 23,24 regulate mitophagy and UPRmt 25–28 and we showed that they were downregulated in both ICM and DCM. Collectively, these data suggest reduced mitochondrial biogenesis in failing human hearts.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…NAD + acts as a substrate of sirtuin enzymes, which have dominant functions in inflammation, metabolism, gene expression, and immune response [18,48,49]. Each sirtuin family member (sirtuins 1-7, or SIRT 1-7) plays an important role in regulating and maintaining the stability of the internal environment of cells, and among these members, SIRT1 has become the most widely studied protein due to its diverse functions, strong deacetyla-tion ability, and high homology with the Saccharomyces cerevisiae transcription regulator Sir2 [50,51]. It has been reported that SIRT1 could increase mitochondrial biogenesis through activating PGC-1α via deacetylation [18,52,53], which plays a dominant part in regulating various mitochondrial proteins.…”
Section: Discussionmentioning
confidence: 99%